Central neuroprotection demonstrated by novel oxime countermeasures to nerve agent surrogates. Issue 1 (21st April 2020) - Chambers, Janice E.; Meek, Edward C.
Abstract: Oximes remain a long‐standing element of the therapy for nerve agents, organophosphates (OPs) that poison by inhibiting the enzyme acetylcholinesterase (AChE), resulting in hypercholinergic activity both centrally and peripherally. Oximes, such as the pyridinium oxime pralidoxime (2‐PAM) in the United States, can reactivate the inhibited AChE and restore cholinergic function. However, there are several drawbacks to the current oximes; one of them, the inability of these oximes to effectively enter the brain, is the subject of study by several laboratories, including ours. Our laboratory invented a platform of substituted phenoxyalkyl pyridinium oximes that were tested against highly relevant surrogates of the nerve agents, sarin and VX. Using high sublethal dosages of the OPs, the novel oximes were observed to attenuate seizure‐like behavior in rats and to reduce the levels of glial fibrillary acidic protein (an indicator of glial scarring) to control levels, in contrast to levels observed with 2‐PAM or no oxime therapy. Using lethal levels of surrogates, some novel oximes protected against lethality compared with 2‐PAM, shortened the time to cessation of seizure‐like behavior (from 8+ to 6 h), and protected the brain neurons. Therefore, some of these novel oximes are showing exceptional promise alone or in combination with 2‐PAM as therapeutics against nerve agent toxicity. Abstract : Our laboratory invented a platform of substituted phenoxyalkyl pyridinium oximes that were tested against highly relevant surrogates of the nerve agents, sarin and VX. Using high sublethal dosages of the organophosphates, they were observed to attenuate seizure‐like behavior in rats and to reduce the levels of glial fibrillary acidic protein to control levels, in contrast to levels observed with 2‐PAM or no oxime therapy. Using lethal levels of surrogates, some novel oximes protected against lethality, compared with 2‐PAM, shortened the time to cessation of seizure‐like behavior and protected the brain neurons.